High-strength plastic super-corrosion-resistant magnesium alloy and preparation method thereof

By adjusting the composition and preparation process of magnesium alloy, the second phase of small and uniform distribution is formed, which solves the problem that the magnesium-aluminum alloy corrosion resistance and strong plasticity are difficult to improve at the same time. Magnesium alloy.

CN119351841APending Publication Date: 2025-01-24JILIN UNIVERSITY

Patent Information

Application Number
CN202411467553.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During solidification, magnesium-aluminum alloys are prone to form a coarse second phase with high melting points, resulting in a reduced corrosion resistance and it is difficult to simultaneously improve the strong plasticity and corrosion resistance of the alloy.

Method used

By adjusting the ingredients and preparation of magnesium alloy, it is specifically included in the protection of hexarial sulfurizer and carbon dioxide mixed gas to heat pure magnesium, add preheated pure aluminum, tin and other elements, and perform high -purity mixing, diagonal plate tilt angle casting and rolling , Steps such as staircase solid -soluble and multi -tract rolling, forming a second phase of small and uniform distribution.

Benefits of technology

The effective regulation of the second phase, size, and distribution in the alloy, significantly reduced the micro -electrical puppet corrosion between the second phase and the matrix, and improved the strength, plasticity and corrosion resistance of the alloy. 3.5 μm, the corrosion rate ≤ 1.9mm/y, the tensile strength ≥ 305MPa, and the extension rate ≥21 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351841A_ABST
    Figure CN119351841A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength plastic super-corrosion-resistant magnesium alloy and a preparation method thereof. The magnesium alloy comprises, by mass, 2%-6% of aluminum, 0.5%-3% of tin, 0.4%-2% of calcium, 0.1%-0.5% of manganese and 0.05%-0.4% of rare earth, the rare earth is one or any combination of yttrium, cerium or samarium, the yttrium is 0.05%-0.4%, the cerium is 0.05%-0.4%, the samarium is 0.05%-0.4%, and the balance magnesium. The content of inevitable impurities is less than or equal to 0.02%. The preparation method of the magnesium alloy comprises the four steps of dip angle cast rolling, stepped solid solution, multi-pass rolling and annealing. According to the method, the process is simplified, the preparation time is effectively shortened, micro-galvanic corrosion between the matrix and the second phase is slowed down, the sizes of the second phase and grains are further reduced, and the corrosion resistance and the strong plasticity of the magnesium alloy are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal materials, and in particular to a high-strength, plastic and super-corrosion-resistant magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium-aluminum alloys have high formability, excellent processing performance, high thermal stability and good creep resistance, but during the solidification process, magnesium easily reacts with aluminum and other elements to form a coarse second phase with a high melting point. The potential difference between these coarse second phases and the magnesium matrix is ​​large, and galvanic corrosion easily occurs between the magnesium matrix, which greatly reduces the corrosion resistance of magnesium alloys and greatly reduces the application value and prospects of magnesium alloys.

[0003] In addition, the second phase in magnesium-aluminum alloy has a high density, large size and irregular shape. It is difficult to eliminate it through conventional heat treatment. Stress concentration is easily generated during the subsequent deformation process, which greatly damages the mechanical properties of the alloy and makes it difficult to improve the strength and plasticity of the alloy simultaneously. It can be seen that it is difficult to achieve simultaneous improvement of the strength and plasticity, strength and corrosion resistance, plasticity and corrosion resistance of the alloy. Therefore, how to regulate the size and morphology of microstructures such as coarse second phases and grains in the alloy without damaging the corrosion resistance of the alloy, and further improve the strength and plasticity of the alloy is a key issue that needs to be solved urgently. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a high-strength, plastic and super-corrosion-resistant magnesium alloy. The magnesium alloy is composed of the following components by mass percentage: aluminum: 2-6%, tin: 0.5-3%, calcium: 0.4-2%, manganese: 0.15-0.5%, rare earth: 0.05-0.4%, the inevitable impurity content is ≤0.02%, and the balance is magnesium; the rare earth is one or any combination of yttrium, cerium or samarium, yttrium is 0.05-0.4%, cerium is 0.05-0.4%, and samarium is 0.05-0.4%; the magnesium alloy preparation method comprises:

[0005] (1) Under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, pure magnesium is kept at 500-550° C. for 30-60 minutes, then heated to 700-740° C. and kept for 2-4 hours; pure aluminum, pure tin, magnesium-manganese master alloy, magnesium-calcium master alloy, magnesium-cerium master alloy, magnesium-yttrium master alloy, and magnesium-samarium master alloy preheated at 400-500° C. for 0.5-2 hours are added, and the mixture is stirred at 680-700° C. for 5-20 minutes to obtain a magnesium alloy melt;

[0006] (2) stirring the magnesium alloy melt obtained in step (1) at 600-650° C. for 2-30 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 0.5-5 mL / s, and the high-purity argon stirring device is used to stir the alloy melt with argon gas;

[0007] (3) subjecting the semi-solid slurry obtained in step (2) to inclined plate inclination casting and rolling to obtain a cast-rolled magnesium alloy slab;

[0008] (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to stepwise solid solution treatment and then quenching in warm water at 10-30° C. to obtain a solid solution magnesium alloy slab;

[0009] (5) subjecting the solid solution magnesium alloy slab obtained in step (4) to multiple rolling passes to obtain a rolled magnesium alloy slab;

[0010] (6) subjecting the rolled magnesium alloy slab obtained in step (5) to stress relief annealing and then quenching in warm water at 10-30° C. to obtain a high-strength, plastic, and super-corrosion-resistant magnesium alloy;

[0011] The inclined plate angle casting in step (3) is as follows: the inclined plate material is alumina ceramic fiber, the inclination angle is 5-30°, the inclined plate temperature is set to 500-600°C, and the casting rate is 400-550g / s;

[0012] The step solution treatment in step (4) is as follows: solution treatment at 410-430° C. for 4.5-5.5 h, and then solution treatment at 470-490° C. for 2.5-3.5 h;

[0013] The multi-pass rolling in step (5) is 3-pass rolling, 4-pass rolling or 5-pass rolling; the 3-pass rolling is as follows: the first pass rolling reduction is 25-35%, the second pass rolling reduction is 35-45%, and the third pass rolling reduction is 45-55%; the 4-pass rolling is as follows: the first pass rolling reduction is 18-23%, the second pass rolling reduction is 22-28%, the third pass rolling reduction is 31-37%, and the fourth pass rolling reduction is 45-55%; the 5-pass rolling is as follows: the first pass rolling reduction is 8-12%, the second pass rolling reduction is 18-22%, the third pass rolling reduction is 28-32%, the fourth pass rolling reduction is 38-42%, and the fifth pass rolling reduction is 48-52%;

[0014] The stress relief annealing in step (6) is: keeping the temperature at 200-300° C. for 8-12 minutes;

[0015] The high-strength, plastic, and super-corrosion-resistant magnesium alloy obtained in step (6) has an average grain size of ≤3.5 μm, a corrosion rate of ≤1.9 mm / y, a tensile strength of ≥305 MPa, and an elongation of ≥21%.

[0016] Furthermore, the aluminum is 3-5%, the tin is 1-2.5%, the calcium is 0.7-1.5%, the manganese is 0.25-0.35%, and the rare earth is 0.06-0.15%.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The average grain size of the Mg-Al alloy obtained by the prior art is ≥5.0μm, and there are coarse strip-shaped and block-shaped second phases with a size of about tens of microns inside the alloy, which is not conducive to the improvement of the mechanical properties of the alloy, and the coarse second phase will produce severe galvanic corrosion with the magnesium matrix, with a corrosion rate of ≥2.9mm / y, tensile strength ≤283MPa, and elongation ≤20%. It is difficult to improve any two of strength and plasticity, strength and corrosion resistance, and plasticity and corrosion resistance simultaneously. Compared with the prior art, the present invention can effectively regulate the morphology, size and distribution of the second phase in the magnesium-aluminum alloy while refining the grains, and obtain a fine granular second phase with a size of about hundreds of nanometers. These fine second phases can significantly reduce the micro-galvanic corrosion between the matrix and effectively realize the strengthening of the second phase. The fine and evenly distributed second phase reduces the stress concentration during the deformation process, and simultaneously improves the strength, plasticity and corrosion resistance of the alloy. The average grain size of the magnesium alloy obtained by the present invention is ≤3.5μm, the corrosion rate is ≤1.9mm / y, the tensile strength is ≥305MPa, and the elongation is ≥21%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A comparison of the corrosion resistance of magnesium alloys obtained in Examples 1 to 3 and Comparative Examples 1 to 3;

[0020] Figure 2 This is the stress-strain curve of the alloy obtained in Example 1. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The corrosion resistance of the alloys obtained in the examples and comparative examples was measured in a NaCl solution (with a solution concentration of 3.5% by mass).

[0022] Example 1

[0023] Taking Mg-4Al-1.3Sn-0.7Ca-0.3Mn-0.09Y alloy as an example (according to the composition mass percentage: Al: 4%, Sn: 1.3%, Ca: 0.7%, Mn: 0.3%, Y: 0.09%, unavoidable impurities ≤ 0.02%, the balance is magnesium), its preparation method is as follows:

[0024] (1) Under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, the raw materials were added in batches according to the component ratio, commercial pure Mg was kept at 505°C for 35 minutes, then the temperature was raised to 710°C and kept for 121 minutes; then commercial pure Al, commercial pure Sn, Mg-2Mn master alloy, Mg-25Ca master alloy, and Mg-25Y preheated at 407°C for 33 minutes were added, and the magnesium alloy melt with uniform composition was obtained after stirring at 682°C for 6 minutes and keeping the temperature for 15 minutes;

[0025] (2) stirring the magnesium alloy melt obtained in step (1) at 610° C. for 15 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 0.98 mL / s, and the high-purity argon stirring device is used to stir the alloy melt using argon gas;

[0026] (3) The semi-solid slurry obtained in step (2) is subjected to inclined plate angle casting and rolling, wherein the inclined plate material is alumina ceramic fiber, the inclination angle is 20°, the inclined plate temperature is set to 550°C, and the casting rate is 470 g / s to obtain a cast-rolled magnesium alloy slab.

[0027] (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to solid solution treatment at 421° C. for 5.1 h and then to solid solution treatment at 478° C. for 2.8 h, and quenching in warm water at 23° C. after solid solution treatment to obtain a solid solution magnesium alloy slab;

[0028] (5) The solid solution magnesium alloy slab obtained in step (4) is subjected to four unidirectional rolling passes, wherein the first rolling pass has a rolling reduction of 20%, the second rolling pass has a rolling reduction of 25%, the third rolling pass has a rolling reduction of 33%, and the fourth rolling pass has a rolling reduction of 50%. Before each rolling pass, the slab is kept at 275°C for 10 minutes to obtain a rolled magnesium alloy slab.

[0029] (6) The rolled magnesium alloy slab obtained in step (5) is subjected to stress relief annealing at a temperature of 250° C. for 10 min, and after annealing, it is quenched in warm water at 10-25° C. to obtain a high-strength, plastic, and super-corrosion-resistant Mg-4Al-1.3Sn-0.7Ca-0.3Mn-0.09Y alloy. The average grain size of the alloy is about 2.3 μm, the corrosion rate is as low as 1.3 mm / y (hydrogen evolution rate), the tensile strength is as high as 310 MPa, and the elongation is 23%.

[0030] Example 2

[0031] Taking Mg-4Al-1.2Sn-0.6Ca-0.3Mn-0.1Ce alloy as an example (according to the composition mass percentage: Al: 4%, Sn: 1.2%, Ca: 0.6%, Mn: 0.3%, Ce: 0.1%, unavoidable impurities ≤ 0.02%, the balance is magnesium), its preparation method is as follows:

[0032] (1) Under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, the raw materials were added in batches according to the component ratio, commercial pure Mg was kept at 515°C for 37 minutes, then the temperature was raised to 730°C and kept for 130 minutes; then commercial pure Al, commercial pure Sn, Mg-2Mn master alloy, Mg-25Ca master alloy, and Mg-30Ce preheated at 426°C for 40 minutes were added, and the magnesium alloy melt with uniform composition was obtained after stirring at 685°C for 5 minutes and keeping the temperature for 17 minutes;

[0033] (2) the magnesium alloy melt obtained in step (1) is stirred at 605° C. for 18 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 1.8 mL / s, and the high-purity argon stirring device is used to stir the alloy melt using argon gas;

[0034] (3) The semi-solid slurry obtained in step (2) is subjected to inclined plate angle casting and rolling, wherein the inclined plate material is alumina ceramic fiber, the inclination angle is 22°, the inclined plate temperature is set to 555°C, and the casting rate is 480g / s to obtain a cast-rolled magnesium alloy slab.

[0035] (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to solid solution treatment at 422° C. for 4.9 h and then to solid solution treatment at 487° C. for 3.2 h, and quenching in warm water at 18° C. after solid solution treatment to obtain a solid solution magnesium alloy slab;

[0036] (5) The solid solution magnesium alloy slab obtained in step (4) is subjected to three unidirectional rolling passes, wherein the first rolling pass has a rolling reduction of 21%, the second rolling pass has a rolling reduction of 24%, and the third rolling pass has a rolling reduction of 32%. Before each rolling pass, the slab is kept at 277°C for 15 minutes to obtain a rolled magnesium alloy slab.

[0037] (6) The rolled magnesium alloy slab obtained in step (5) is subjected to stress relief annealing at a temperature of 265° C. for 8 min, and then quenched in warm water at 19° C. to obtain a high-strength, plastic, and super-corrosion-resistant Mg-4Al-1.2Sn-0.6Ca-0.3Mn-0.1Ce alloy. The alloy has an average grain size of about 3.5 μm, a corrosion rate as low as 1.5 mm / y (hydrogen evolution rate), a tensile strength as high as 305 MPa, and an elongation of 21%.

[0038] Example 3

[0039] Taking Mg-4.5Al-1.3Sn-0.8Ca-0.3Mn-0.1Sm alloy as an example (according to the composition mass percentage: Al: 4.5%, Sn: 1.3%, Ca: 0.8%, Mn: 0.3%, Sm: 0.1%, unavoidable impurities ≤ 0.02%, the balance is magnesium), its preparation method is as follows:

[0040] (1) Under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, the raw materials were added in batches according to the component ratio, and commercial pure Mg was kept at 534°C for 41 minutes, and then the temperature was raised to 728°C and kept for 138 minutes; then commercial pure Al, commercial pure Sn, Mg-2Mn master alloy, Mg-25Ca master alloy, and Mg-35Sm, which had been preheated at 412°C for 37 minutes, were added, and the mixture was stirred at 697°C for 5.5 minutes and kept for 13 minutes to obtain a magnesium alloy melt with uniform composition;

[0041] (2) the magnesium alloy melt obtained in step (1) is stirred at 607° C. for 21 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 1.3 mL / s, and the high-purity argon stirring device is used to stir the alloy melt using argon gas;

[0042] (3) The semi-solid slurry obtained in step (2) is subjected to inclined plate angle casting and rolling, wherein the inclined plate material is alumina ceramic fiber, the inclination angle is 19°, the inclined plate temperature is set to 553°C, and the casting rate is 477g / s to obtain a cast-rolled magnesium alloy slab.

[0043] (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to solid solution treatment at 427° C. for 5.3 h and then to solid solution treatment at 477° C. for 2.9 h, and quenching in warm water at 21° C. after solid solution treatment to obtain a solid solution magnesium alloy slab;

[0044] (5) The solid solution magnesium alloy slab obtained in step (4) is subjected to five unidirectional rolling passes, wherein the first rolling pass has a rolling reduction of 18%, the second rolling pass has a rolling reduction of 26%, the third rolling pass has a rolling reduction of 35%, the fourth rolling pass has a rolling reduction of 48%, and the fifth rolling pass has a rolling reduction of 51%; before each rolling pass, the slab is kept at 268°C for 12 minutes to obtain a rolled magnesium alloy slab.

[0045] (6) The rolled magnesium alloy slab obtained in step (5) is subjected to stress relief annealing at a temperature of 261° C. for 8 min, and then quenched in warm water at 20° C. to obtain a high-strength, plastic, and super-corrosion-resistant Mg-4.5Al-1.3Sn-0.8Ca-0.3Mn-0.1Sm alloy. The average grain size of the alloy is about 2.8 μm, the corrosion rate is as low as 1.9 mm / y (hydrogen evolution rate), the tensile strength is as high as 308 MPa, and the elongation is 22%.

[0046] Comparative Example 1

[0047] Taking Mg-1.8Al-0.4Sn-0.3Ca-0.1Mn-0.04Y alloy as an example (according to the composition mass percentage: Al: 1.8%, Sn: 0.4%, Ca: 0.3%, Mn: 0.1%, unavoidable impurities ≤ 0.02%, the balance is magnesium), its preparation method is as follows:

[0048] (1) Under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, the raw materials are added in batches according to the component ratio, and commercial pure Mg is kept at 560°C for 25 minutes, and then the temperature is raised to 690°C and kept for 110 minutes; then commercial pure Al, commercial pure Sn, Mg-2Mn master alloy, Mg-25Ca master alloy, and Mg-25Y that have been preheated at 390°C for 25 minutes are added, and the mixture is stirred at 710°C for 5 minutes and kept for 22 minutes to obtain a magnesium alloy melt with uniform composition;

[0049] (2) the magnesium alloy melt obtained in step (1) is stirred at 680° C. for 3 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 0.2 mL / s, and the high-purity argon stirring device is used to stir the alloy melt using argon gas;

[0050] (3) The semi-solid slurry obtained in step (2) is subjected to inclined plate casting and then angle casting and rolling, wherein the inclined plate material is alumina ceramic fiber, the inclination angle is 35°, the inclined plate temperature is set to 620°C, and the casting rate is 650g / s to obtain a cast-rolled magnesium alloy slab;

[0051] (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to solid solution treatment at 380° C. for 6 h and then at 520° C. for 1 h, and quenching in warm water at 5° C. after solid solution treatment to obtain a solid solution magnesium alloy slab;

[0052] (5) The solid solution magnesium alloy slab obtained in step (4) is subjected to four unidirectional rolling passes, wherein the first rolling pass has a rolling reduction of 10%, the second rolling pass has a rolling reduction of 30%, the third rolling pass has a rolling reduction of 40%, and the fourth rolling pass has a rolling reduction of 55%. Before each rolling pass, the slab is kept at 276°C for 11 minutes to obtain a rolled magnesium alloy slab.

[0053] (6) The rolled magnesium alloy slab obtained in step (5) is subjected to stress relief annealing at a temperature of 180° C. for 13 min, and then quenched in warm water at 14° C. to obtain a high-strength, plastic, and super-corrosion-resistant Mg-1.8Al-0.4Sn-0.3Ca-0.1Mn-0.04Y alloy. The alloy has an average grain size of about 5.0 μm, a corrosion rate of 2.9 mm / y, a tensile strength of 283 MPa, and an elongation of 16%.

[0054] Comparative Example 2 (Invention name: A high-strength and high-corrosion-resistant magnesium alloy and its preparation method; Inventors: Yue Qichi, Liao Qiyu, Cheng Chunlong, Jiang Yanchao, Hu Chenglu, Chen Xingrui; Publication number: CN109881061A))

[0055] Taking Mg-8Al-0.5Zn-0.1Mn-1.2La-0.6Ce alloy as an example (according to the mass percentage: Al: 8.0%, Zn: 0.5%, Mn: 0.1%, La: 1.2%, Ce: 0.6%, unavoidable impurities ≤ 0.04%, the balance is magnesium), the preparation method is as follows:

[0056] (1) preparing a magnesium ingot, a zinc block, an aluminum block, manganese chloride particles and a Mg-rich La-mixed rare earth master alloy, wherein the Mg-rich La-mixed rare earth master alloy contains 30% La and 30% Ce by weight, and the weight ratio of La / Ce is 2:1; the particle size of the manganese chloride particles is 1 to 3 mm;

[0057] (2) the prepared No. 5 flux is 0.2% of the total weight of the magnesium ingot, zinc block, aluminum block, manganese chloride and Mg-La-rich mixed rare earth master alloy;

[0058] (3) Under protective atmosphere conditions, the magnesium ingot is added into a smelting resistance furnace for melting, and the melting temperature is set to 750±5°C to obtain a magnesium melt; the protective atmosphere is an argon atmosphere;

[0059] (4) melting the aluminum block in another smelting resistance furnace under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3 at a melting temperature of 750±5°C to obtain an aluminum melt; adding zinc blocks, manganese chloride particles and Mg-rich La mixed rare earth master alloys to the aluminum melt in sequence, and adding No. 5 flux at the same time, and after all the materials are melted, a mixed melt is obtained;

[0060] (5) adding the mixed solution to a magnesium melt under the protection of a mixture of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, refining at 750±5°C for 30 minutes, and then standing for 30 minutes, cooling to 700°C during the standing process to prepare a magnesium alloy melt;

[0061] (6) using an electromagnetic semi-continuous casting system to cast the magnesium alloy melt, and starting the electromagnetic system to electromagnetically stir the magnesium alloy melt and the ingot at the beginning of the casting, with the electromagnetic frequency being 15 to 30 Hz, until the casting is completed to obtain a magnesium alloy ingot;

[0062] (7) placing the magnesium alloy ingot in a muffle furnace and then performing a double-stage homogenization treatment; wherein the temperature of the first-stage homogenization treatment is 180° C. and the time is 8 h; the temperature of the second-stage homogenization treatment is 350° C. and the time is 15 h; after the double-stage homogenization treatment, the surface oxide scale is removed to obtain an ingot;

[0063] (8) The ingot was kept at 280°C for 3 h and then hot extruded on a vertical extruder. The extrusion outlet speed was 0.2 mm / s. The temperature of the extrusion barrel and the die during hot extrusion was 280°C. The extrusion ratio was 15:1. The magnesium alloy obtained after hot extrusion had a corrosion rate of 3.8 mm / y and an elongation of 20%.

[0064] Comparative Example 3: (Invention name: A high-strength corrosion-resistant magnesium alloy; Inventors: Ying Tao, Zhou Yinpeng, Wang Shiyi, Li Dejiang, Luo Yunbin, Zhao Hua, Zeng Xiaoqin; Publication number: CN106834852A)

[0065] Taking Mg-6Sc-0.6Mn-0.7Zr alloy as an example (according to the mass percentage: Sc: 6.0%, Mn: 0.6%, Zr: 0.7%, unavoidable impurities ≤ 0.04%, and the balance is magnesium), the preparation method is as follows:

[0066] (1) Material preparation and furnace cleaning: Prepare materials according to the composition ratio of the magnesium alloy and clean the furnace; wherein the Sc element is added in the form of a Mg-Sc master alloy, the Mn element is added in the form of a single element or a Mg-Mn master alloy, and the Zr element is added in the form of pure Zr or a Mg-Zr master alloy;

[0067] (2) Melting of magnesium ingots: All pure magnesium ingots are placed as tightly as possible into a pit-type resistance crucible furnace, sulfur powder is evenly sprinkled on the bottom of the crucible and the surface of the pure magnesium ingots, the crucible is sealed with a crucible cover, a protective gas composed of SF6 and N2 is introduced, and the temperature is raised to completely melt all the pure magnesium ingots under sulfur dioxide and the protective gas, and the temperature of the magnesium melt is controlled at 700-780°C;

[0068] (3) Adding the master alloy: When the temperature of the magnesium melt reaches above 710° C., the dried Mg-Mn master alloy and Mg-Zr master alloy are added to the magnesium melt. The temperature of the magnesium melt is raised to 750° C., and the Mg-Sc master alloy is added to the magnesium melt. The temperature is kept at this temperature for 15 minutes to ensure that all the added master alloys are melted, thereby obtaining a magnesium alloy liquid.

[0069] (4) Alloy refining: When the temperature of the magnesium melt rises to above 730°C, a special refining agent for magnesium alloy is added to start refining. During the refining process, the refining spoon is immersed in 2 / 3 of the magnesium alloy liquid, and the magnesium alloy liquid is stirred vigorously from top to bottom until the liquid surface shows a mirror-like luster. During the stirring process, the special refining agent for magnesium alloy is continuously sprinkled on the surface of the magnesium alloy liquid. After the refining is completed, the solvent and scum on the liquid surface are removed, and then a layer of covering agent is lightly sprinkled. The temperature is cooled to an appropriate temperature and allowed to stand until the inclusions fully float up or sink, and finally the slag is skimmed.

[0070] (5) Alloy extrusion: The magnesium alloy was extruded at an extrusion ratio of 16:1 and a temperature of 300° C. The magnesium alloy obtained after hot extrusion had a corrosion rate of 8.5 mm / y and an elongation of 10%.

[0071] Compared with comparative examples 1-3, the mechanical properties and corrosion resistance of the alloy obtained by the present invention are higher than those of the alloy obtained by the comparative examples. Although comparative example 1 uses similar components and processes as the present invention, its component ratio and process parameters are not within the scope of claim 1 of the present invention, resulting in its mechanical properties and corrosion resistance being lower than the minimum mechanical properties and corrosion resistance of the alloy obtained by the present invention; in addition, the rare earth content and total element addition amount used in comparative examples 2 and 3 are higher than the element content added by the present invention, and the processes used in comparative examples 2 and 3 are different from those of the present invention. In addition, the component ratio and process parameters used in each embodiment of the present invention are different, among which the component addition amount of embodiment 1 is not the highest, but the mechanical properties and corrosion resistance are the highest, which shows that the most excellent performance of the alloy obtained by the present invention is not determined by a certain component or process or process parameter, but is achieved by the interaction of components, component ratio, process and process parameters. The reasons for the excellent effects achieved by the present invention mainly include: first, effectively reducing the galvanic corrosion between the second phase and the matrix in the alloy, and enhancing the stability and density of the corrosion product film of the alloy in the NaCl solution (measured by mass percentage, the solution concentration is 3.5%), inhibiting further corrosion of the alloy, and improving the corrosion resistance of the alloy; second, it can effectively regulate the morphology, size and distribution of the second phase in the alloy, and the finely distributed second phase can reduce the stress concentration during the deformation process. The obtained alloy has a uniform fine-grained structure (average grain size ≤3.5μm), thereby significantly improving the plastic deformation ability of the alloy. At room temperature, the alloy has an elongation at break of ≥21%, a tensile strength of ≥305MPa and corrosion resistance (hydrogen evolution rate ≤1.9mm / y).

[0072] In summary, the present invention achieves a synergistic regulation of alloy interactions, alloy ratios, processes and process parameters, and only when the relevant parameters are within the protection scope of the claims of the present invention can the strength, plasticity and corrosion resistance of the alloy be improved simultaneously, thus breaking the technical bottleneck in the prior art that it is difficult to simultaneously improve any two of the strength, plasticity and corrosion resistance of alloys.

Claims

1. A high-strength, plastic, and corrosion-resistant magnesium alloy, characterized in that: The magnesium alloy is composed of the following components by mass percentage: aluminum: 2-6%, tin: 0.5-3%, calcium: 0.4-2%, manganese: 0.15-0.5%, rare earth: 0.05-0.4%, the inevitable impurity content is ≤0.02%, and the balance is magnesium; the rare earth is one or any combination of yttrium, cerium or samarium, yttrium is 0.05-0.4%, cerium is 0.05-0.4%, and samarium is 0.05-0.4%; The magnesium alloy preparation method comprises: (1) Under the protection of a mixed gas of sulfur hexafluoride and carbon dioxide in a volume ratio of 1:99-1:3, pure magnesium is kept at 500-550° C. for 30-60 minutes, then heated to 700-740° C. and kept for 2-4 hours; pure aluminum, pure tin, magnesium-manganese master alloy, magnesium-calcium master alloy, magnesium-cerium master alloy, magnesium-yttrium master alloy, and magnesium-samarium master alloy preheated at 400-500° C. for 0.5-2 hours are added, and the mixture is stirred at 680-700° C. for 5-20 minutes to obtain a magnesium alloy melt; (2) stirring the magnesium alloy melt obtained in step (1) at 600-650° C. for 2-30 min using a high-purity argon stirring device to obtain a semi-solid slurry, wherein the gas inlet rate is 0.5-5 mL / s, and the high-purity argon stirring device is used to stir the alloy melt with argon gas; (3) subjecting the semi-solid slurry obtained in step (2) to inclined plate inclination casting and rolling to obtain a cast-rolled magnesium alloy slab; (4) subjecting the cast-rolled magnesium alloy slab obtained in step (3) to stepwise solid solution treatment and then quenching in warm water at 10-30° C. to obtain a solid solution magnesium alloy slab; (5) subjecting the solid solution magnesium alloy slab obtained in step (4) to multiple rolling passes to obtain a rolled magnesium alloy slab; (6) subjecting the rolled magnesium alloy slab obtained in step (5) to stress relief annealing and then quenching in warm water at 10-30° C. to obtain a high-strength, plastic, and super-corrosion-resistant magnesium alloy; The inclined plate angle casting in step (3) is as follows: the inclined plate material is alumina ceramic fiber, the inclination angle is 5-30°, the inclined plate temperature is set to 500-600°C, and the casting rate is 400-550g / s; The step solution treatment in step (4) is as follows: solution treatment at 410-430° C. for 4.5-5.5 h, and then solution treatment at 470-490° C. for 2.5-3.5 h; The multi-pass rolling in step (5) is 3-pass rolling, 4-pass rolling or 5-pass rolling; the 3-pass rolling is as follows: the first pass rolling reduction is 25-35%, the second pass rolling reduction is 35-45%, and the third pass rolling reduction is 45-55%; the 4-pass rolling is as follows: the first pass rolling reduction is 18-23%, the second pass rolling reduction is 22-28%, the third pass rolling reduction is 31-37%, and the fourth pass rolling reduction is 45-55%; the 5-pass rolling is as follows: the first pass rolling reduction is 8-12%, the second pass rolling reduction is 18-22%, the third pass rolling reduction is 28-32%, the fourth pass rolling reduction is 38-42%, and the fifth pass rolling reduction is 48-52%; The stress relief annealing in step (6) is: keeping the temperature at 200-300° C. for 8-12 minutes; The high-strength, plastic, and super-corrosion-resistant magnesium alloy obtained in step (6) has an average grain size of ≤3.5 μm, a corrosion rate of ≤1.9 mm / y, a tensile strength of ≥305 MPa, and an elongation of ≥21%.

2. A high-strength, plastic, and super-corrosion-resistant magnesium alloy according to claim 1, characterized in that: The aluminum is 3-5%, the tin is 1-2.5%, the calcium is 0.7-1.5%, the manganese is 0.25-0.35%, and the rare earth is 0.06-0.15%.

Citation Information

Patent Citations

  • High-strength corrosion-resistant magnesium alloy

    CN106834852A

  • High-strength and high-resistance-to-corrosion magnesium alloy and preparation method thereof

    CN109881061A

Cited By

  • High-flame-retardant high-thermal-conductivity magnesium alloy and preparation method thereof

    CN122214727A